Une adaptation de l’approche modulaire au phénomène des ponctuants du discours - Simon, Anne-Catherine (Travaux neuchâtelois de linguistique, 1999)
This paper focuses on a kind of discourse particles called "ponctuants". The "ponctuants" are defined by Diane Vincent (1992) as prosodical cues for the discourse structure. I have tried to propose a model of analysis suitable for this king of particles. Indeed, it is difficult to characterize the discourse "ponctuants" because their function in verbal interaction can only be explained by refering to a body of convergent factors. The modular mode (approche modulaire) recently developped by Roulet (1995) is very relevant: different modules allow us to consider the function of the "ponctuants" in verbal interaction.